1989
DOI: 10.1007/bf01871722
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the use of the lipophilic thiocyanate anion for the determination of membrane potential in Ehrlich ascites tumor cells

Abstract: The utility of the lipophilic anion thiocyanate (SCN-) as a probe for the indirect estimation of the cell membrane potential (Vm) in Ehrlich ascites tumor cells has been evaluated by comparison to direct electrophysiological measurements. SCN accumulation is consistent with first-order uptake into a single, kinetically-identifiable cellular compartment, achieving steady-state distribution in 20-30 min at 22 degrees C. The steady state distribution ratio ([SCN-]e/[SCN-]e) in physiological saline is 0.44 +/- 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…Because of the cell shrinkage induced by A23187, this hyperpolarization is slightly underestimated, although the effect of the volume changes is probably small. Membrane hyperpolarization in Ehrlich cells is similarly seen after addition of propranolol, which is known to activate Ca2+-dependent K + channels (Laris et al, 1976;Valdeolmillos, Garcia-Sancho & Herreros, 1986;Smith & Robinson, 1989). It was previously demonstrated that A23187 activated separate, conductive K § and C1 pathways and we find in the present report that the increase in GK and Gcl are 13 and 50 times, respectively, after addition of A23187 (see Table 3).…”
Section: Membrane Conductancessupporting
confidence: 72%
See 2 more Smart Citations
“…Because of the cell shrinkage induced by A23187, this hyperpolarization is slightly underestimated, although the effect of the volume changes is probably small. Membrane hyperpolarization in Ehrlich cells is similarly seen after addition of propranolol, which is known to activate Ca2+-dependent K + channels (Laris et al, 1976;Valdeolmillos, Garcia-Sancho & Herreros, 1986;Smith & Robinson, 1989). It was previously demonstrated that A23187 activated separate, conductive K § and C1 pathways and we find in the present report that the increase in GK and Gcl are 13 and 50 times, respectively, after addition of A23187 (see Table 3).…”
Section: Membrane Conductancessupporting
confidence: 72%
“…8). A similar depolarization is observed in Ehrlich cells when the potassium channels are inhibited by addition of Ba 2+ (Gstrein et al, 1987;Smith & Robinson, 1989).…”
Section: Membrane Conductancessupporting
confidence: 51%
See 1 more Smart Citation
“…The membrane potentiel ( V m ) was estimated by measuring the extra‐ over intracellular distribution ratios of [ 14 C]SCN – (Catterall et al . 1976; Smith and Robinson 1989; Bettendorff and Wins 1994).…”
Section: Methodsmentioning
confidence: 99%